Comparison of Saccharomyces cerevisiae strains of clinical and nonclinical origin by molecular typing and determination of putative virulence traits - Klingberg, Trine Danø; Lesnik, Urska; Arneborg, Nils; Raspor, Peter; Jespersen, Lene (FEMS yeast research, 2008)
Saccharomyces cerevisiae strains of clinical and nonclinical origin were compared by pulse field gel electrophoresis. Complete separation between strains of clinical origin and food strains by their chromosome length polymorphism was not obtained even though there was a tendency for the clinical and food strains to cluster separately. All the investigated strains, except for one food strain, were able to grow at temperatures >=37 °C but not at 42 °C. Great strain variations were observed in pseudohyphal growth and invasiveness, but the characters were not linked to strains of clinical origin. The adhesion capacities of the yeast strains to a human intestinal epithelial cell line (Caco-2) in response to different nutritional availabilities were determined, as were the effects of the strains on the transepithelial electrical resistance (TER) across polarized monolayers of Caco-2 cells. The yeast strains displayed very low adhesion capacities to Caco-2 cells (0.6-6.2%), and no significant difference was observed between the strains of clinical and nonclinical origin. Both S. cerevisiae strains of clinical and non-clinical origin increased the TER of polarized monolayers of Caco-2 cells. Based on the results obtained in this study, no specific virulence factor was found that clearly separated the strains of clinical origin from the strains of nonclinical origin. On the contrary, all investigated strains of S. cerevisiae were found to strengthen the epithelial barrier function.